Renal Calculi as Initial Presenting Symptom of Glycogen Storage Disease (Type 1 A) in Early Infancy - Mirza, Nida; Malhotra, Smita; Sibal, Anupam (Journal of Child Science, 2020)
Glycogen storage diseases are a group of heterogeneous metabolic disorders that result from a defect in enzymatic pathway of either glycogen synthesis or glycogen degradation. Here we are reporting a case of glycogen storage diseases type 1 with renal stone as initial manifestation of disease at 2 months of age. There were case reports of recurrent renal calculi in older age group with this disease and considered to be arisen due to metabolic derangements. Although the exact mechanism of renal stones in glycogen storage disease is not clear, in this unique case occurrence of renal stones at 2 months of age suggests that the pathogenesis of renal calculi is probably multifactorial or a part of disease.
Keywords: renal calculi; early infancy; glycogen storage disease